Legal Protection for Indonesian Migrant Workers Against Online Scam–Based Human Trafficking - Andita, Berliana Putri; Yitawati, Krista; Haryani, Anik Tri (Potret Pemikiran, 2025)
This study examines the legal protection of Indonesian migrant workers as a vulnerable group against online scam–based human trafficking through a normative and regulatory analysis that integrates human rights and socio-religious perspectives. The research is motivated by the rapid transformation of trafficking practices into digitally mediated forced criminality, which exposes migrant workers to recruitment through fraudulent online platforms and exploitation in transnational cyber-scam operations. Using a normative juridical method combined with an interdisciplinary socio-legal approach, this study analyzes national legislation, international instruments, and ASEAN regional mechanisms to identify regulatory gaps, assess state responsibility, and evaluate victim protection frameworks. The findings reveal three major issues: fragmentation between migration, anti-trafficking, and cybercrime laws; limitations in international and regional cooperation, particularly in victim identification and the application of the non-punishment principle; and the absence of culturally and religiously responsive protection mechanisms. The study further demonstrates that Muslim Indonesian migrant workers experience intersectional vulnerability as migrants, low-wage laborers, and religious minorities, while Islamic community networks function as informal yet effective protection and rehabilitation systems. This research proposes a rights-based and socio-religious model of legal protection that integrates digital governance, normative harmonization, and the institutional recognition of faith-based organizations within national and regional referral mechanisms. The study contributes to the discourse on the protection of vulnerable groups, regulatory transformation, and transnational cyber exploitation by offering a holistic legal framework that responds to the evolving nature of technology-facilitated trafficking.